Enfermedad inflamatoria muscular - Castañeda J. , Oswaldo (1979)
Twenty five patients meeting the Bohaq & Peter's criteria for the diagnosis of either Polymyositis or Dermatomyositis are presented. All but 2 of them were female.  Definitive Dermatomyositis and Polymyositis associated to Connective Tissye Disease were the two larger groups. There was no case of myositis associated with malignancy.  Eventhough muscle weakness was not the earliest complaint, it was the most common reason for the patients to seek medical consultation.  Results are discussed and compared with world literature, including factors regarding final outcome.  The need for an early diagnosis is stressed out in order to provide adequate therapy and improve prognosis in these patients.